Arctic Environmental Test of Individual Weapons Rifles (Semi-Automatic and Automatic) and Pistols - ARMY TEST AND EVALUATION COMMAND ABERDEEN PROVING GROUND MD (1969)
The objective of the procedures is to provide a means of evaluating the performance of individual weapons (rifles and pistols) under arctic winter environmental conditions.